Igneous Rock Associations 9. Ophiolites 1: From the Beginning to Modern Times - Hébert, Réjean (Geoscience Canada, 2007)
SUMMARY This paper on ophiolites is the first of four that will appear in Geoscience Canada; it reviews a fascinating history dating back to the very first, glorious days of field mapping in the western Alps in the 1800s. Originally used to describe serpentinites, the term ophiolite progressively evolved to designate a field association (rock clan) of peridotites, gabbros, and radiolarites. Early on, the deep ocean origin of this association was recognized. Recognition of the ophiolitic rock clan in North America was late, due to conflicts among field geologists, experimental petrologists, and marine geologists. The advent of plate tectonic theory helped put the ophiolitic rock clan in the right geodynamic context with respect to mountain belts. Also, the clan was expanded to include pillow lavas, sheeted dikes, abyssal sedimentary rocks, and other metamorphic units. Starting in 1957, it was clear that the basal peridotites were partly derived from the upper mantle and some others derived by crystal fractionation processes, as defined by Bowen. This basal peridotite and the rest of the rock clan constituted the so-called Penrose-type stratigraphy as defined in 1972. Since then, countless studies have shown that ophiolites are transported sheets, a concept fitting plate tectonic theory and the Wilson cycle. Still debated is the geodynamic significance of ophiolites. Are they produced in large ocean basins at mid-ocean ridges or in more confined settings like forearcs, arcs or back-arc basins close to continental margins? Decades of research have shown that Penrose-type ophiolitic sequences can be produced in a variety of geodynamic settings and with complex geochemical attributes. This new approach led to the possibility that ophiolites could be present throughout the geological column and particularly in Precambrian terrains. Originally thought to begin in Neoproterozoic time, ophiolite sequences are now thought to be found in the Archean but those older than 1 Ga have different stratigraphy and geo-chemical compositions. However, these differences are currently matters of debate. The new concept of Precambrian ophiolites might shed light on the early mechanisms controlling the mobile parts of the Earth.